AN OBSERVATIONAL STUDY ON THE OUTCOME OF ANTITUBERCULAR AND ANTIDIABETIC THERAPY IN PATIENTS OF TUBERCULOSIS WITH DIABETES MELLITUS AS COMORBIDITY - JEENAL MISTRY; ANITA SINHA; B DIVAKAR; NAYAN GAVLI; PARUL VADGAMA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Overall goal: To observe and compare the effect of antitubercular and antidiabetic therapy on patients of tuberculosis with diabetes mellitus as comorbidity. To study the effect of antidiabetic therapy on treatment outcome of tuberculosis. To study the effect of antitubercular drugs on glycemic control of patients of tuberculosis with diabetes mellitus Methods: A total of 134 patients of tuberculosis with and without diabetes mellitus were approached for enrollment in this prospective observational cohort study as per NTEP guidelines. Effects of antitubercular therapy on antidiabetes drugs and vice versa during this study were observed and noted. A comparison of outcomes between two groups of patients of tuberculosis with diabetes and tuberculosis without diabetes was done according to outcome parameters. Results: Mortality was found in patients on ATT+ADD nearly 11.94% (n=8) as compared to patients on ATT only 2.98% (n=2). Delayed sputum conversion with higher sputum positive rate (1+) among patients on ATT+ADD (23.89%) and mean HbA1c value at the end of the continuous phase (CP) was 6.7±1.07 among patients on ATT+ADD. Conclusion: The patients on ATT+ADD have higher sputum positivity rates and poor treatment outcomes as compared to patients on ATT alone. Poor glycemic control in patients receiving ATT+ADD unfavorably leads to poor compliance with antitubercular therapy.